2022
DOI: 10.3390/su142114557
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Aged Asphalt Pavement Binder through Rejuvenators

Abstract: Natural resources are declining due to rising infrastructure, renovation, demolition, and recycling of existing structures that necessitate sustainable development. It urges the researchers to modify the aged asphalt binder in the recycling to enhance the performance life of asphaltic pavements. The aim of this research study is to reutilize recycled materials through rejuvenation. This study utilizes the Cereclor to rejuvenate the aged binder collected from recycling and explore its transformation by comparin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Yaseen, G. et al, Chen, A.Q. et al and Bilema, M. et al [17][18][19] surveyed the influence of rejuvenator content on penetration, softening point and ductility of recycled asphalt. Researchers investigated the microscopic mechanism of aged asphalt with rejuvenator, and it was found that the composition of aged asphalt changed by the rejuvenator, the light components decreased and the micelle number and proportion in the colloidal structure increased [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Yaseen, G. et al, Chen, A.Q. et al and Bilema, M. et al [17][18][19] surveyed the influence of rejuvenator content on penetration, softening point and ductility of recycled asphalt. Researchers investigated the microscopic mechanism of aged asphalt with rejuvenator, and it was found that the composition of aged asphalt changed by the rejuvenator, the light components decreased and the micelle number and proportion in the colloidal structure increased [20,21].…”
Section: Introductionmentioning
confidence: 99%